Pyrolysis and kinetic analysis of marine (Isochrysis sp.) and freshwater (Monoraphidium c.) microalgae - Noridah B. Osman; Umi Syahirah Binti Mohd Amin; David Onoja Patrick; Nurul Asyikin Binti Badir Noon Zaman; Syazmi Zul Arif Hakimi Saadon; Suzana Yusup; Liyana Yahya (Energy Conversion and Management: X)
Marine and freshwater microalgae grow in two different ecosystems, which influence their properties thus requires attention prior to determining its application. This paper has successfully disclosed the thermal, chemical, and physical properties of two types of microalgae on carbon dioxide (CO2) fixation and underwent pyrolysis process. Slow pyrolysis process for marine and freshwater microalgae (Isochrysis sp. and Monoraphidium c.) was performed in the fixed bed pyrolysis reactor and TGA (thermogravimetric analyzer) to determine the product yield and study their thermal decomposition profile. The pyrolysis was completed at various temperatures (400, 450, 500, and 550 °C) at a heating rate of 15°Cmin−1 and nitrogen flow rate of 200 ml min−1. Pyrolysis in TGA analyzer ran from 27 to 800 °C at three heating rates (10, 20, and 40 °Cmin−1). For chemical composition, Fourier-transform Infrared (FTIR) analysis was performed on both microalgae samples. The highest yield (up to 33.9 %) of bio-oil was obtained from Isochrysis sp. for all temperatures while the highest average yield (65.78 %) of biochar was collected from Monoraphidium c. species. From TGA pyrolysis, the major decomposition occurred between 200–400 °C for Monoraphidium c. species. On the other hand, the decomposition profile of Isochrysis sp. was slightly slower, which may be due to the differences in lipid composition (FTIR peak 2929 cm−1). The activation energy of all tests is lower (33.6–40.3 kJ mol−1) compared to several other biomasses. Marine species fixed with CO2 showed promising results even without addition of catalyst and no additional cost needed.